ANALISIS PEMECAHAN MASALAH SISWA PADA MATERI PERBANDINGAN BERDASARKAN PROSEDUR NEWMAN - Matuankotta, Agnes; Laurens, Theresia; Tamalene, Hanisa (Atom : Jurnal Riset Mahasiswa, 2024)
Problem solving analysis is the process of sorting or investigating a problem from complex to simple by paying attention to the rules and logical steps in order to find a solution to a problem using adequate understanding and knowledge, so that the problem being sorted or investigated can be resolved. well and correctly. Based on the results of the researcher's interview with one of the mathematics subject teachers in class VII of SMP Negeri 8 Ambon, it was found that during the learning process on comparative material, many students were able to work on questions but only the questions were the same as the examples given and explained by the teacher. The aim to be achieved in this research is to describe the process of student problem solving on comparative material based on the Newman procedure in class VII of SMP Negeri 8 Ambon. The type of research used is qualitative descriptive research. This research describes the comparative problem solving process based on the Newman procedure. The subjects in this research were 2 students with the initials TK and JKL who were chosen with consideration, students answered all questions correctly based on problem solving indicators, and students who were able to communicate well and according to the considerations of teachers at the school. Based on the results of the problem solving test and interview results, it was found that both subjects were capable of solving problems according to the problem solving indicators